Safety of perioperative aprotinin administration during isolated coronary artery bypass graft surgery: Insights from the ART (Arterial Revascularization Trial) - Benedetto, U; Altman, DG; Gerry, S; Gray, A; Lees, B; Angelini, GD; Flather, M; Taggert, DP; on behalf of the ART investigators (American Heart Association, 2018)
Background: There is still uncertainty about the safety of aprotinin for coronary artery bypass graft (CABG) surgery. The Arterial Revascularization Trial (ART) was designed to compare survival after bilateral vs single internal thoracic artery grafting. A large proportion of the ART patients (~30%) received perioperative aprotinin. We investigated the association between perioperative Aprotinin administration and short (in-hospital) and long-term outcomes by performing a post-hoc analysis of the ART. Methods: Among patients enrolled in the ART (n=3102) from 2004 to 2007, we excluded those who did not undergo surgery (n=18) and those with no information regarding use of perioperative aprotinin (n=9). Finally, 836 out of 3076 patients (27%) received aprotinin. Propensity score matching (1:1) selected 536 pairs for final comparison. Conditional logistic and stratified Cox models were used to investigate treatment effect on short and long-term outcomes respectively. Results: Hospital mortality was significantly higher in the Aprotinin group (9,1.7% vs 1,0.2%; Odds ratio, OR: 9.12; 95% confidence interval CI 1.15-72.2; P=0.03). Aprotinin was also associated with an increased risk of intra-aortic balloon pump insertion (37, 6.9% vs 17, 3.2%; OR 2.26; 95%CI 1.26-4.07; P=0.006) and acute kidney injury (102, 19.0% vs 76, 14.2%; OR 1.42; 95%CI 1.03-1.97; P=0.03). We also found a non-significantly increased risk of in hospital reintervention in the Aprotinin group (7, 1.3% vs 2,0.4%; OR 3.53 95%CI 0.73-17.1; P=0.1). Aprotinin was not associated with a lower incidence of red blood cell transfusion (37, 6.9% vs 28, 5.2%; OR 1.34; 95%CI 0.81-2.23; P=0.25). and re-exploration (26, 4.9% vs 19, 3.5%; HR 1.39; 95%CI 0.76-2.53; P=0.28). At 5 years, all-cause mortality was significantly increased in the Aprotinin group (56, 10.6% vs 38, 7.3%; Hazard ratio 1.51; 95% CI 1.0-2.28; P=0.045). Conclusions: In the present post-hoc ART analysis, Aprotinin was associated with a significantly increased risk of early and late mortality.